Customer Satisfaction in Traditional Shopping in the ERA of M. Commerce: Exploring customer preferences and satisfaction in traditional and online shopping (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The aim of the study is to decide the customer's satisfaction to buy traditional and for knowledge output at supermarkethypermarket stores. Online shopping is nevertheless stress-free for users and less costly than traditional shopping. When shopping a shopper can consider whether to buy digitally or to shop traditionally. The consumer can pick for them a shopping model that will better match and meet their needs. In this economical environment it is really important for consumers to consider from a management point of view how the particular medium for their transaction is.